PREVALENCE AND OUTCOME OF POSTPARTUM HAEMORRHAGE IN TERTIARY CARE HOSPITAL - Amna Begum; Arifa Jabeen; Tasneem Kousa; Israr Ali khan (Journal of Population Therapeutics and Clinical Pharmacology, 2020)
Background: The most terrifying event a woman may anticipate is death during childbirth, which continues to be the predominant cause of maternal mortality. Postpartum Haemorrhage is a common problem in less developed countries like Pakistan. Objective: To assess the prevalence and outcome of Postpartum Haemorrhage in tertiary care hospital Methodology: The current cross-sectional study was carried out at Pir Sayed Abdul Qadir Shah jilani institute of medical sciences Gambat. The duration of our study was six months from December 2019 to May 2020. In order to determine the frequency of PPH, all the deliveries were recorded during the study duration. Following written informed permission, demographic information including age, gestational age, and parity was entered into a pre-made proforma. For the data analysis we use SPSS version 24. Results: In the current study, a total of 250 women were included. The mean age (SD) in the current study was 28 (4.32) years. The overall frequency of postpartum hemorrhage was 10 (4%). Amongst the 10 patients with postpartum hemorrhage, 8 (80%) patients were had primary postpartum hemorrhage while 2 (20%) patients had secondary postpartum hemorrhage. Based on causes of postpartum hemorrhage, uterine atony was observed in 5(50%) patients, perineal and vaginal tears in 3 (30%) and prolonged labor was observed in 2 (10%) patients. Based on outcomes, out of 10 postpartum hemorrhage patients, 1 (10%) women were observed with DIC and 1 (10%) patient had pulmonary edema. The overall mortality rate was 1 (10%). Conclusion: Our study concludes that the frequency of postpartum haemorrhage is high with a prevalence of 4%. Primary PPH was common as compared to secondary PPH. The major cause of PPH was Uterine atony